ADA, promoting telecom industries by triggering emotional and cultural sentiments related to current global issues for brand marketing - Aurin, Shenjuti Mahmud (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.